Pengaruh kemiskinan, pendidikan, dan kesehatan terhadap pertumbuhan ekonomi di Jawa Tengah pada era Ganjar Pranowo - Ayumna, Frida Salma; Sukardi, Agung Slamet (Nur Science Institute, 2024)
This research aims to determine the influence of poverty, education, and health on economic growth in Central Java during the Ganjar Pranowo era. This research uses a quantitative approach, and the data comes from BPS Central Java Province. The analysis technique used is multiple regression analysis. The research results show that poverty hurt increasing economic growth in Central Java Province during the Ganjar Pranowo era. However, other results show that education does not affect economic growth in Central Java. Other findings also show that health has a negative effect on economic growth.